The Rise In Gold Prices And Its Implications For MSME Financial Management - Dodi Yuli Satria; Delsi Desrianti; Salsabila Zahra; Hasyifa Suwanda Putri; Widi Nugraha (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The increase in gold prices in 2025 will be a significant economic phenomenon with a broad impact on various sectors, including Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the implications of the increase in gold prices on MSME financial management and formulate appropriate management strategies in response to these dynamics. The method used is a literature study by reviewing relevant national and international scientific literature, supported by Indonesian gold price data for 2025. The results show that the increase in gold prices increases the value of MSME assets and has the potential to strengthen their financial position, but also poses liquidity risks if not balanced with good cash flow management. In addition, gold can serve as a hedge against inflation and economic uncertainty, but it still requires an asset diversification strategy and careful financial planning. Therefore, strengthening financial literacy, disciplined record keeping, the use of digital technology, and rational investment planning are key to optimizing the benefits of rising gold prices. This study confirms that the integration of gold into MSME financial management must be done proportionally and strategically to support business stability and sustainability.